Analytical fourier approximation of five-phase vector modulation voltage source inverter / Mohammad Afiq Othman - Othman, Mohammad Afiq (2013)
To utilize AC machine with phase number higher than three, electric drives in power electronic applied. For various applications, multiphase motor usage considered as typical solution. Multiphase drives are invariably supplied from multiphase voltage source inverters and adequate methods for VSI pulse width modulation (PWM) are therefore required. Proper modelling of voltage source inverters is important in devising appropriate control algorithm. This paper study of a five phase voltage source inverters based on space vector approach. The existing technique is elaborated utilizing only large space vectors. The Fourier analysis of output phase to neutral voltage, line to line voltage, and pole voltage are performed for ten step mode of operation (large vector). Simulation results are included throughout the paper to illustrate and verify the theoretical calculation.